2015
DOI: 10.1364/oe.23.027865
|View full text |Cite
|
Sign up to set email alerts
|

Cellular dye lasers: lasing thresholds and sensing in a planar resonator

Abstract: Biological cell lasers are promising novel building blocks of future biocompatible optical systems and offer new approaches to cellular sensing and cytometry in a microfluidic setting. Here, we demonstrate a simple method for providing optical gain by using a variety of standard fluorescent dyes. The dye gain medium can be located inside or outside a cell, or in both, which gives flexibility in experimental design and makes the method applicable to all cell types. Due to the higher refractive index of the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 29 publications
1
55
0
Order By: Relevance
“…The biological cells here provide a crucial role to facilitate lasing, which would otherwise be difficult to attain due to misalignment of the cavity mirrors. As shown in Figure d,e, the cells act as a microlens, and so can stabilize the laser resonator by redirecting the diffracted rays toward the optical axis . To test the effectiveness of the cells in stabilizing the laser resonator, the experiment was repeated with the cells and supernatant sandwiched between two glass slides with one of the slides tilted at an angle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological cells here provide a crucial role to facilitate lasing, which would otherwise be difficult to attain due to misalignment of the cavity mirrors. As shown in Figure d,e, the cells act as a microlens, and so can stabilize the laser resonator by redirecting the diffracted rays toward the optical axis . To test the effectiveness of the cells in stabilizing the laser resonator, the experiment was repeated with the cells and supernatant sandwiched between two glass slides with one of the slides tilted at an angle.…”
Section: Resultsmentioning
confidence: 99%
“…Reflectance at the walls is indeed very poor and external agents such as microbeads or scattering nanoparticles/nanocrystals are not introduced in the system. Humar and Yun reported that cell lasers consisting of dye‐doped cells embedded between two high reflective distributed Bragg reflector (DBR) mirrors, in an all‐similar experimental setup with ns pulsed pump laser, display a laser threshold of ≈45 nJ per pulse . In such a case DBR mirrors provided the light confinement required for amplification, and the cells play only a minor role in reducing the laser thresholds owing to a thoroughly described “lens effect” .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2e. Such Q-factor degradation is less significant in the case of single-cell lasers due to the lensing effect of the cell 14 . Unfortunately, this lensing effect may not exist for tissue lasers when cells are embedded in the extracellular matrix.…”
Section: Resultsmentioning
confidence: 99%
“…These properties have been harnessed for ultrasensitive sensing [3], spectral multiplexing [4] and sub-diffraction microscopy [5]. Examples of biological lasers include hybrid lasers containing cells [6,7] and tissues [8] inside Fabry-Pérot cavities, microlasers inside cells [4,9] and random lasers [10] in tissues [11]. Lasers made entirely from biomaterials were also demonstrated.…”
Section: Introductionmentioning
confidence: 99%